Signifikansi Budaya Pada Restorasi Arsitektur Dan Interior Pemedal Agung Dan Penyengker Pura Desa Dan Pura Puseh Desa Adat Denpasar - Pranajaya, I Kadek; Artayasa, I Nyoman; Winaja, I Wayan (Jurnal Penelitian Agama Hindu, 2024)
Many temples in Bali have been renovated without regard to their historical value, resulting in many new forms, ornaments, and materials even though the temple as a cultural heritage has cultural, social, and religious values. This research aimed to examine the reasons and process of restoring Pemedal Agung and Penyengker in the Pura Desa (Village Temple) and Pura Puseh (Puseh Temple) of Denpasar Traditional Village and analyze the restoration implementation implications of Pemedal Agung and Penyengker in the Pura Desa and Pura Puseh of Denpasar Traditional Village. This research used qualitative methods through a case study and ethnographic approach. The results showed that the causal factors in Denpasar Traditional Village restoring Pemedal Agung and Penyengker in the Pura Desa and Pura Puseh were due to a shared understanding of the importance of the traces and historical values in the temple building. It was outlined in the Perarem (rules) regarding the procedures for the temple repair process, and the community understands the importance of Denpasar’s identity value. The restoration stages and process of Pemedal Agung and Penyengker in the Pura Desa and Pura Puseh of Denpasar Traditional Village began with the planning process, identification of building form and damage, technical document preparations, procurement of construction workers, restoration implementation, and periodic supervision. The restoration process was accompanied by a series of Balinese Hindu ritual processes, namely Nuntun, Ngeruak, Mendem Pedagingan, Ngingsirang Pretime, and Ngeteg Linggih ceremonies. The restoration implications of Pemedal Agung and Penyengker in the Pura Desa and Pura Puseh of Denpasar Traditional Village could provide cultural significance, such as aesthetic, social, and religious values, with substantial cultural and symbolic capital.